A novel, efficient and economical alternative for the removal of toxic organic, inorganic and pathogenic water pollutants using GO-modified PU granular composite. (1st July 2023) - Sahu, Prateekshya Suman; Verma, Ravi Prakash; Dabhade, Ajinkya Hariram; Tewari, Chetna; Sahoo, Nanda Gopal; Saha, Biswajit
Abstract: Multicomponent wastewater treatment utilising simple and cost-effective materials and methods is an important research topic. This study has reported the fabrication and utilisation of graphene oxide (GO) embedded granular Polyurethane (PU) (GOPU) adsorbent for the treatment of lead ion (Lead ion (Pb(II)), Methylene blue (MB), and E. coli . PU granules were wrapped with GO flakes to improve hydrophilicity, interaction with polluted water, cation-exchange reaction, and binding of pollutants on its surface. Synthesised GOPU granules were characterised by X-Ray Diffraction (XRD), Raman, Fourier transform infrared (FTIR) spectroscopy, and Scanning electron microscopy (SEM) analysis to ensure the successful synthesis of GO and fabrication of GOPU granules. Further, batch and continuous adsorption processes were studied in different operating conditions to evaluate the performance of GOPU granules in practical applications. The kinetic and isotherm analyses revealed that the adsorption of Lead (Pb(II)) ion and Methylene Blue (MB) dye followed the Freundlich and Langmuir isotherm models, respectively, and they showed good agreement with the Pseudo-second-order kinetic model. The adsorption capacities of GOPU granules for the elimination of Pb(II) and MB dye were about 842 mg/g and 899 mg/g, respectively. Additionally, investigations into the fixed bed column revealed that the adsorption column performed best at a flow rate of 5 mL/min and a bed height of 6 cm. Pb(II) adsorption had a bed uptake capacity (qbed ) of 88 mg/g and percentage removal efficiency (%R) of 76%. Similarly, MB adsorption had a bed uptake capacity of 202 mg/g and a percentage removal efficiency of 71%. A systematic invention on antibacterial activity toward E. coli showed that The GOPU granules have a removal efficiency of about 100% at an exposure of 24 h. These findings indicated the possible use of GOPU granules as promising adsorbents for various water pollutants. Graphical abstract: Image 1 Highlights: GOPU granular could be a cost-effective industrial alternative. Various organic, inorganic, and pathogenic pollutants were treated using GOPU. Model calculations illustrate the material's utmost adsorption capacity. Batch and fixed-bed column studies were carried out to evaluate GOPU's Pb(II) and MB removal efficiency. GOPU granules showed excellent antibacterial activity for the removal of E. coli.